DEVELOPMENT AND RELIABILITY OF SCRATCH PROJECT: VISUAL OPERATIONS FOR TOPIC INDICES FORM THREE - Muhammad Adam Che Jamil; Shazlyn Milleana Shaharudin; Florencea Roslin; Farida Nurhasanah; Muzaffar Eshnazarovich Nurillaev; Xayrullayev Davron Baxodir oʻgʻli (Program Studi S1 Pendidikan Matematika FKIP Universitas Bengkulu, 2026)
This study investigates the development and reliability of a Scratch-based software teaching aid, Visual Operations, designed to enhance secondary school students' understanding of indices in mathematics. Utilizing the ADDIE model, this research emphasizes the integration of computational and visual thinking to address challenges in mathematics education. The study employs a quantitative research design, targeting 84 Form Three students and four expert validators, to ensure the software's effectiveness. Instruments included need analysis, validity, and reliability questionnaires, and data were analyzed using SPSS software. Findings reveal that the software achieved a Content Validity Index (CVI) of 1.00 and a Cronbach’s Alpha coefficient exceeding 0.80, indicating high validity and reliability. The interactive and visual features of the software significantly enhanced student engagement and understanding of indices. The implications highlight the potential for such softwares to transform mathematics education, fostering critical 21st-century skills. Future research should explore potential and long-term impacts.